(untitled) (Kathmandu University Medical Journal, 2012)
Background The clavicle is the most frequently fractured bone of the human skeleton. 70–80% of fractures occur at the middle third of the shaft of the bone. Anatomical variations in the clavicle of relevance to form intramedullary fixation. Objectives The purpose of this study was attempted to know about comparative differences between curvatures of the right and left clavicles, from certain metrical parameters. Methods The materials for the present study consisted of 257 (135 right and 122 left) adult clavicles, which were collected from the Department of Anatomy and from the students of the first year M.B.B.S during the period 2010 - 2011, Department of Anatomy, Kathmandu University School of Medical Sciences, Dhulikhel, Nepal. The deepest points of the curvatures of the clavicle, where the convexities were the maximum. These angles were measured with the help of a protractor. The sum of the two angles constituted the total curvature of the bone. Results The average medial angle, lateral angle and sum of the two angles of right side were 150.97º ±6.16 SD, 139.76º ±7.55 SD and 290.73º ±11.14 respectively and that of the left side were 151.50º ±5.67SD, 141.73º ±8.44 SD and 293.23º ±11.69SD respectively. The present study revealed that the medial and lateral angles of the left clavicle were greater than that of the right clavicle and medial curvature was more than the lateral curvature of the same clavicle. Conclusions It is important to recognize anatomical variations in the curvatures of clavicle when considering intramedullary nailing techniques. It also helps Anthropologists in their study of evolution. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6344 Kathmandu Univ Med J 2011;9(4):279-82